A New Aesthetic for a New Bauhaus. (EAAE Annual Conference Proceedings, 2023)
It seems possible that in recent times the concept of the architectural aesthetic has come to be treated with a certain amount of distrust. There is, I think, a perception that the term ‘aesthetic’ has become shorthand for the implication that when an architectural language – it doesn’t matter which language – is evident in a work it only serves to remind us that in the world of spatial arrangement there are those who get to determine the aesthetic and those for whom aesthetics are determined.